GAYA KEPEMIMPINAN KEPALA DESA DI DESA TANETE KECAMATAN BONTOMATENE KABUPATEN SELAYAR - Tasbih, Nur; Madani, Muhlis; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study purposed to find out the leadership style of the village head of Tanete, Selayar Regency. This study used  a qualitative descriptive study. Data collection techniques were observation, interview, and documentation techniques. The data validity technique used was triangulation. The results of the study  on the Leadership Style of the Village Head in Tanete Village, Selayar Regency, seen from the Telling aspect, showed that the Tanete Village Head applied it by considering the maturity level of its members who were ready to be led and carried out responsibilities as instructed, the selling aspect showed that the Tanete Village Head gave an explanation. In more detail on the responsibilities that must be carried out by its members, one of which took into account the age factor of its members, the Participating aspect showed that the Tanete Village Head was not only about the participation of leaders in government performance, but also related to the leader's efforts to encourage, motivate, and involve members in the deliberation process, as well as decision making, the Delegating aspect showed that the Tanete Village Head carried out the functions of observing, supervising, and resolving the performance of its members.Keywords: Leadership Style, Village Head